The difficulties of schooling of students with disabilities in a hospital environment (Research, Society and Development, 2018)
The difficulties of the schooling of students with disabilities in a hospital environment is a very important issue and it still needs to be studied, since the number of  PAEE students (target public of special education) has increased in schools and in the hospital environment, generating difficulties in the performance of the professional. Thus, this article aims to investigate the history of special education and hospital and to identify the challenges of schooling of students with disabilities in the hospital environment, also exposing ways to overcome these challenges. In this way a bibliographic research was carried out from electronic books, official documents and scientific articles accessible in reliable websites and databases, to increase knowledge and provide information that helps the professional to work in the best possible way. For now, the paths covered by special education and hospital, the challenges they face and how to overcome them are highlighted, which may contribute in the future to the best performance of professionals in the area. It is provisionally concluded that inclusion in both the school and the hospital environment still requires research, since it is a current issue that causes insecurity in relation to how to act, given the lack of necessary professional training.